Automatic Calibration of the Adaptive 3D Scanner-Based Robot Welding System - Arko, Peter; Jezeršek, Matija (Frontiers in Robotics and AI, 2022)
An advanced automatic calibration procedure and its versatile usage in the context of adaptive robot welding technology are presented. 3D scanner-based robot welding system calibration is composed of measurement of the reference plate and numerical optimization of the hand-eye and intrinsic parameters by minimizing deviation between measured and reference plate. The measurements of the reference plate are acquired from various robot poses (typically 15). The shape features of the reference plate are then detected, and finally, the calculation of hand-eye and intrinsic parameters is performed using Powell`s optimization algorithm, where the merit function presents an average deviation between measured and reference geometry. Validation experiments show appropriate system accuracy which is better than 0.06 mm perpendicular to the scanning direction. This calibration procedure's important feature is complete automation and fast execution times (approximately 90 seconds). This enables its implementation into a regular daily robot self-maintenance and monitoring plan. The universal use of such a robot welding system is demonstrated on multi-layer heavy-duty welding of thick pipes on casted machined hollow parts, and on precise laser welding of thin sheet metal parts.